Individualistic and Structural Explanations in Ásta’s Categories We Live By - Aaron Griffith (Journal of Social Ontology, 2022)
Ásta’s Categories We Live By is a superb addition to the literature on social metaphysics. In it she offers a powerful framework for understanding the creation and maintenance of social categories. In this commentary piece, I want to draw attention to Ásta’s reliance on explanatory individualism – the view that the social world is best explained by the actions and attitudes of individuals. I argue that this reliance makes it difficult for Ásta to explain how many social categories are maintained and why certain categories are reliably available to us and so resistant to change. These explanatory deficiencies could be overcome, I argue, by eschewing explanatory individualism and positing social structures to figure in structural explanations of the maintenance and availability of social categories.